LONG-TERM OUTCOMES OF LIGATION OF INTERSPHINCTERIC FISTULA TRACT FOR COMPLEX FISTULA-IN-ANO: MODIFIED OPERATIVE PROCEDURE EXPERIENCE - WEN,Ke (2018)
ABSTRACT Background: It is important but difficult to treat complex fistula-in-ano due to the high recurrent rate and following incontinence. Ligation of the intersphincteric fistula tract (LIFT), a novel surgical procedure with the advantage of avoiding anal incontinence, has a variable success rate of 57-94.4 %. Aim: To evaluate the long-term outcomes of modified LIFT operative procedure - ligation of intersphincteric fistula tract - to treat complex fistula-in-ano. Methods: Retrospective analysis of 62 cases of complex fistula-in-ano. The group was treated with the modified approach of LIFT (curved incision was made in the anal canal skin; purse-string suture was performed around the fistula; the residual fistulas were removed in a tunnel-based way) and had a follow-up time of more than one year. Patient´s preoperative general condition, postoperative efficacy and their anal function were compared. Results: The median age of the participants was 34, and 43 (69.4%) cases were male. Forty-one (66.1%) cases were of high transsphincteric fistula, four (6.5%) cases of high intrasphincter fistula, and 17 (27.4%) cases of anterior anal fistula in female. The median follow-up duration was 24.5 (range, 12-51) months. The success rate in the end of follow-up was 83.9% (52/62). The anorectal pressure and Cleveland Clinic Florida Fecal Incontinence (CCF-FI) evaluated three months before and after the operation did not find apparent changes. Conclusions: Compared with LIFT, the modified LIFT remarkably reduces postoperative failure and the recurrence rate of complex fistula with acceptable long-term outcomes.